Pengaruh Senam Lansia Terhadap Lansia Dengan Hipertensi di UPTD Puskesmas Sei Lekop Kabupaten Bintan - Tilukman Tilukman; Siska Natalia; Wulan Pramadhani (Pusat Riset dan Inovasi Nasional, 2024)
In the elderly, the cardiovascular system will experience changes, such as arteries losing their elasticity, which can cause an increase in pulse and systolic blood pressure. Elderly exercise utilizes movement by activating the sympathetic and parasympathetic nervous systems and increasing the release of various hormones which cause the individual's condition to relax. Elderly exercise is a physical activity that is useful for eliminating fat and cholesterol in blood vessels. This exercise is rarely carried out routinely at research sites. The aim of this study was to determine the effect of elderly exercise on hypertension in the elderly at the Sei Lekop Community Health Center. This study used a pre-experimental research design with a one group pre-post test design with probability sampling, involving 31 elderly people with hypertension. Blood pressure was measured with a spygmomanometer and elderly exercise was carried out according to procedures. Data analysis was carried out using paired t-test. The results showed that the average blood pressure before the intervention was 150.00/94.48 mmHg, whereas after the intervention the average blood pressure was 140.48/90.48 mmHg, with a p value = 0.001 for systolic pressure and 0.003 for diastolic pressure, so it was proven that there was a significant influence on blood pressure before and after the elderly exercise intervention was given to the elderly at the Sei Lekop Community Health Center. It is hoped that elderly exercise can be used and become a work program at the Community Health Center which is carried out routinely for both elderly people with hypertension and those who are healthy.